A Life-Cycle Consumption Model with Liquidity Constraints: Theory and Empirical Results - Mariger, Randall P. (Econometrica, 1987)
A structural consumption model incorporating endogenous liquidity constraints is fit to a cross section of 798 U.S. families. Liquidity constrained families are estimated to constitute 19.4 percent of the population sampled, a group that accounts for 16.7 percent of consumption in the population sampled. In-sample simulations of the model suggest that a temporary tax has three to four times more impact on aggregate consumption than it would if liquidity constraints were not in effect. Copyright 1987 by The Econometric Society.